2006
DOI: 10.1063/1.2352046
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow resistance-area product of 0.4Ω(μm)2 and high magnetoresistance above 50% in CoFeB∕MgO∕CoFeB magnetic tunnel junctions

Abstract: An ultralow resistance-area (RA) product of 0.4Ω(μm)2 was achieved in CoFeB∕MgO∕CoFeB magnetic tunnel junctions with a high magnetoresistance ratio of 57% at room temperature. Various growth conditions for polycrystalline MgO(001) tunneling barrier were optimized to improve the crystalline orientation of the MgO(001) layer, which resulted in a significant enhancement of magnetoresistance in an ultralow RA region below 1Ω(μm)2. Removal of residual H2O molecules from a growth chamber was especially effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 15 publications
1
60
0
1
Order By: Relevance
“…Without IR heat treatment, which is shown as green circles, TMR ratio gradually decreases from 200 % with decreasing of RA product leading to the TMR ratio of 100 % and the RA product of 5 Ωµm 2 . Such the tendency is consistent with the previous reports [10][11]. In contrast, for the samples with IR heat treatment, which is shown as red circles, the TMR ratio at low RA product region less than 10 Ωµm 2 is significantly improved.…”
Section: Enhancement Of Mr Ratio At Low Ra Region In Cofeb/mgo/cofebsupporting
confidence: 92%
“…Without IR heat treatment, which is shown as green circles, TMR ratio gradually decreases from 200 % with decreasing of RA product leading to the TMR ratio of 100 % and the RA product of 5 Ωµm 2 . Such the tendency is consistent with the previous reports [10][11]. In contrast, for the samples with IR heat treatment, which is shown as red circles, the TMR ratio at low RA product region less than 10 Ωµm 2 is significantly improved.…”
Section: Enhancement Of Mr Ratio At Low Ra Region In Cofeb/mgo/cofebsupporting
confidence: 92%
“…Instead it is the deposition of MgO that causes oxidation of the electrode. Thus we attribute the increased control and quality of MTJs with MgO͓rf͔ barriers that is achieved by inclusion of an Mg layer 3,4 and by deposition of a Ta gettering layer before MgO͓rf͔ deposition 14,15 to the capture of oxygen liberated from the MgO target in the early stages of sputtering.…”
Section: X-ray Photoemission Study Of Cofeb / Mgo Thin Film Bilayersmentioning
confidence: 97%
“…However, in 2005, Djayaprawira et al found that high TMR can also be achieved with a CoFeB/MgO/CoFeB system [28] in which the amorphous CoFeB layer promotes a strong (001) textured growth of the MgO. Later, Nagamine et al [29] showed that >50 % TMR at 0.4 Omm 2 can be achieved for CoFeB/MgO/CoFeB. This enabled the use of MgO barriers in magnetic recording read heads.…”
Section: Growth and Processing Of Tunneling Magnetoresistance Sensorsmentioning
confidence: 94%